Avaliação de parâmetros cardiovasculares e desempenho cognitivo de estudantes de ambientes inteligentes de ensino submetidos à variação de temperatura do ar - Siqueira, Joseana Celiza Fernandes (2015)
Several institutions have issued alerts about the rise in global temperature in the past few years, and on its tendency to keep rising in the future. This temperature rise has been associated to human deaths, some of which related to cardiovascular dysfunctions, and to loss of physical and cognitive performance on humans. Purpose: To analyze the relation between cardiovascular parameters (blood pressure and heart rate) and cognitive performance of students submitted to changes of temperature in classrooms. Methods: The university students answered the survey adapted of Battery of Reasoning Tests (BPR-5) during three consecutive days in different temperatures, while thermal conditions and heart rate were measured. In these days, the blood pressure and the heart rate were evaluated before and after the test. Results: The blood pressure did not alter with different temperatures during cognitive activity. However, the average heart rate and the final increased at high temperatures. The accuracy of cognitive performance was not altered with changes of temperature, on the other hand, the execution time reduced at high temperatures. Using the analyzes by Generalized Linear Models, it was observed that the accuracy on cognitive test was related to mean blood pressure at the beginning of the test, the maximum heart rate during the test and the air temperature. Conclusion: This research concluded that accuracy in cognitive performance rises from 70% to 75%.when the students are submitted to temperatures which them consider neutral and maximum heart rate and mean blood pressure are compatible with activity.